Dynamic Study of a Predator-Prey Model with Weak Allee Effect and Delay - Yong Ye; Hua Liu; Yu-mei Wei; Ming Ma; Kai Zhang (Advances in Mathematical Physics)
In this paper, a prey-predator model and weak Allee effect in prey growth and its dynamical behaviors are studied in detail. The existence, boundedness, and stability of the equilibria of the model are qualitatively discussed. Bifurcation analysis is also taken into account. After incorporating the searching delay and digestion delay, we establish a delayed predator-prey system with Allee effect. The results show that there exist stability switches and Hopf bifurcation occurs while the delay crosses a set of critical values. Finally, we present some numerical simulations to illustrate our theoretical analysis.